Analisis Yuridis Terhadap Implementasi Kewenangan Peradilan Agama Dalam Penyelesaian Sengketa Ekonomi Syariah - Nur Hijriah; Dzulkifli Al'Amin; Hardianti Hardianti; Mafthu Ikhsan; Nurul Huda (Al-Azhar Islamic Law Review, 2026)
The growth of the sharia economic sector in Indonesia continues to develop along with the increasing activities of financial institutions and businesses based on sharia principles. This development has the potential to give rise to various sharia economic disputes among the parties involved. In this regard, the Religious Courts have the authority to examine, adjudicate, and resolve sharia economic disputes as regulated in Law Number 3 of 2006 and Law Number 50 of 2009 concerning Religious Courts. This study aims to juridically analyze the implementation of the authority of Religious Courts in resolving sharia economic disputes and the effectiveness of its implementation in judicial practice. The method used in this research is normative legal research with statutory and conceptual approaches supported by library research. The results indicate that the Religious Courts have a strategic role in resolving sharia economic disputes due to clear legal foundations and the application of sharia principles in judicial processes. However, several obstacles remain, including limited human resource competence and the low level of public understanding regarding the authority of the Religious Courts.